Investigating Causing Factors of Speaking Anxiety - Arief Styo Nugroho; Roro Tunjung Sari; Habib Cahyono; Puji Siswanto; Obay Jambari (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research was conducted to find out what factors affect the English anxiety of 11th-grade students of AKL SMK PGRI Rangkasbitung. In particular, the researchers tried to identify the internal and external factors that can influence students' anxiety in learning English based on internal and external perspectives. The method used in this research is the descriptive qualitative method. Ten students were selected as participants. Data were collected through questionnaires. The results showed that students' anxiety was divided into internal and external factors. Shame, lack of self-confidence, memory dissociation, and stage fear are internal factors. Grammar ability, vocabulary, students' reading skills, and peers are included as external factors.